Using ICTs to disseminate Agricultural Marketing Information to Small Scale Rural Farmers in Western Uganda - Miwanda, Albert; Kabaale, Edward; Mayoka Kituyi, Geoffrey (International Journal of Innovative and Applied Research, 2014)
Although ICT has been extensively used in agriculture in the developed world for agricultural marketing information dissemination, the same cannot be claimed in developing countries. Hence this study sought to explore the extent to which Information and Communication Technologies enhances small scale rural farmer’s access to Agricultural marketing information in western Uganda. This is due to the fact that majority of small scale farmers in Uganda have limited access to market information and usually rely on information from traders (middlemen) who usually twist the information in their favor in order to exploit the farmers. A mixed research approach was used in this study for data collection where a total of 280 farmers, 2 sub county agricultural officials and 3 agriculture facilitators in Millennium Villages Project (Ruhiira) staff members were purposively selected in this study. The study yielded a 75% response rate and the data collected were analyzed using Statistical Package for Social Sciences (SPSS). It was established that most respondents preferred Radio followed by cell phones as their sources of agricultural marketing information for their produce. Television and computer were the least preferred sources of market information by the respondents. The study also found out that most farmers use agricultural marketing information accessed through ICTs as a base for bargaining with buyers for their farm produce.
Keywords: ICTs; Agriculture; Marketing information; Dissemination; Small scale rural farmers